2017
DOI: 10.1093/ee/nvx187
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering in the Bamboo Mosquito Tripteroides bambusa (Diptera: Culicidae) During a Warm, But Unpredictably Changing, Winter

Abstract: The bamboo mosquito, Tripteroides bambusa (Yamada) (Diptera: Culicidae), is a common insect across forested landscapes in Japan. Several studies have reported its overwintering as larvae and eggs, in both natural and artificial water containers. Nevertheless, it is unclear how sensitive this mosquito species is to changes in weather patterns associated with global warming. The El Niño event of 2015 through 2016 was one of the strongest on record and provided an ideal scenario for observations on the overwinter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…One potential limitation of this study was the use of weather data from KC’s weather station, which was around 12 km apart from the study sites. Our previous experience has been that over spatial scales similar to the one of this study [ 68 , 95 ], and even larger [ 71 ] temperature fluctuations are more synchronous than mosquito abundance, and very similar to observations from weather stations located at a distance similar to the one between KC’s weather station and our study locations [ 95 ]. Based on that, we believe data from KC’s weather station was appropriate to evaluate the association between weather fluctuations and mosquito abundance at the two study sites.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…One potential limitation of this study was the use of weather data from KC’s weather station, which was around 12 km apart from the study sites. Our previous experience has been that over spatial scales similar to the one of this study [ 68 , 95 ], and even larger [ 71 ] temperature fluctuations are more synchronous than mosquito abundance, and very similar to observations from weather stations located at a distance similar to the one between KC’s weather station and our study locations [ 95 ]. Based on that, we believe data from KC’s weather station was appropriate to evaluate the association between weather fluctuations and mosquito abundance at the two study sites.…”
Section: Discussionsupporting
confidence: 82%
“…aegypti and Cx. quinquefasciatus , especially considering this study was done during one of the strongest ENSO events on record [ 66 , 67 ], which altered weather patterns at KC ( Supplementary Figure S2 [Online Only]), and also altered weather and phenological patterns of mosquitoes elsewhere in east Asia, as documented for Tripteroides bambusa (Yamada) in Nagasaki, Japan, where the comparison of records from the 1970’s and 1980’s with data from 2016 and 2017 showed an increase in winter temperatures and that pupal recruitment season has lengthened its duration [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that human landing catch is the best method to sample adult mosquitoes in the Neotropics [42], we think our study could have benefited by using other sampling methods for the adult populations, such as Mosquito Magnet ® traps [102]. Also, our environmental data could have been more descriptive of the local environmental conditions of our sampling sites if our budget had allowed us to use data loggers measuring local weather variables [103] instead of resorting to spatially coarsely grained records from gridded databases. We also think that a more frequent sampling, for example, biweekly instead of monthly, could have been helpful to straightforwardly link patterns of larvae and adult abundance, which at the monthly time scale, were not significantly correlated with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic stages, i.e., pupae, large (4th instar) and small (1st, 2nd and 3rd instar) larvae, were sampled between 14 June 2014, and 24 June 2015 (28 sampling sessions), provided Tr. bambusa overwinters as larvae [77]. Fourteen sampling sessions, conducted between 18 May and 15 November 2014, covered the adult activity season [14].…”
Section: Methodsmentioning
confidence: 99%
“…bambusa adults have a crucial trait that is characteristic of major zoonotic pathogen vectors, the ability to bloodfeed on diverse host species [73]: humans, domestic mammals, birds, and reptiles [74]. Also, the bamboo mosquito seems to have a very plastic biology, as it can reproduce autogenously, i.e., without bloodfeeding on a vertebrate host [75] and overwinter as both eggs and 4th instar larvae [76,77].…”
Section: Introductionmentioning
confidence: 99%